Effects of Global Warming on Berry Composition of cv. Sangiovese: Biochemical and Molecular Aspects and Agronomical Adaptation Approaches - Movahed, Nooshin <1985> (Alma Mater Studiorum - Università di Bologna, 2013)
Wine grape must deal with serious problems due to the unfavorable climatic conditions resulted from global warming. High temperatures result in oxidative damages to grape vines. The excessive elevated temperatures are critical for grapevine productivity and survival and contribute to degradation of grape and wine quality and yield. Elevated temperature can negatively affect anthocyanin accumulation in red grape. Particularly, cv. Sangiovese was identified to be very sensitive to such condition. The quantitative real-time PCR analysis showed that flavonoid biosynthetic genes were slightly repressed by high temperature. Also, the heat stress repressed the expression of the transcription factor “VvMYBA1” that activates the expression of UFGT. Moreover, high temperatures had repressing effects on the activity of the flavonoids biosynthetic enzymes “PAL” and “UFGT”.Anthocyanin accumulation in berry skin is due to the balance between its synthesis and oxidation. In grape cv. Sangiovese, the gene transcription and activity of peroxidases enzyme was elevated by heat stress as a defensive mechanism of ROS-scavenging. Among many isoforms of peroxidases genes, one gene (POD 1) was induced in Sangiovese under thermal stress condition. This gene was isolated and evaluated via the technique of genes transformation from grape to Petunia. Reduction in anthocyanins concentration and higher enzymatic activity of peroxidase was observed in POD 1 transformed Petunia after heat shock compared to untrasformed control. Moreover, in wine producing regions, it is inevitable for the grape growers to adopt some adaptive strategies to alleviate grape damages to abiotic stresses. Therefore, in this thesis, the technique of post veraison trimming was done to improve the coupling of phenolic and sugar ripening in Vitis vinifera L. cultivar Sangiovese. Trimming after veraison showed to be executable to slow down the rate of sugar accumulation in grape (to decrease the alcohol potential in wines) without evolution of the main berry flavonoids compounds.